PEMBERANTASAN MAFIA PERADILAN DENGAN PEMBERDAYAAN âGAYA SENTRIFUGALâ DAN âSENTRIPETALâ UKUM DALAM PENEGAKAN SUPREMASI HUKUM (Suatu Kontemplasi Refleksif) - Gunakaya, A. Widiada (Jurnal Wawasan Yuridika, 2010)
Judicial corruption in Indonesia is offenses beyond the reach of the law, Its growth is systemic, not just individual form of corruption, but also shaped, structural, institutional, and political corruption. Such crimes, it can disrupt and inhibit the development of law, hinder the achievement of objectives of the law, threatening the whole system of law, undermine the legal guidance and law enforcement officials, as well as damaging the quality of law enforcement in a fair and dignified. Mitigation efforts should integrate efforts and Penal nonpenal simultaneously. In the law enforcement policy, the instrumental anticorruption law should be empowered to implement the "centrifugal force" laws, and legal position imperatively must be centered and focused in the community, both as adresat legal arrangements and the rule of law. In order to streamline law enforcement, is necessary to reform anticorruption law, which is done by applying the "centripetal force" laws, and laws should be interpreted as a subsocial systems that influence and determine the legal establishment.Keywords: Judicial Corruption - "sentri fugal force of law" - "style petal sentri law"